Answer:
Step-by-step explanation:
Because you have to take the L.C.M ,
-9/5 - 1
=( -9-5)/5
= -14/5
please
Brain-list it or support me at my U-Tube channel " ZK SOFT&GAMING " I will be thankful
Since I just realized that you meant x^2-2x+1, let me evaluate this step by step:
x^2-2x+1
((-3)^2)-(2(-3))+1
9-(-6)+1
9+6+1
16
Therefore, that would equal 16.
Answer:
32
Step-by-step explanation:
To complete the square you halve the coefficient of the x term and square it. Half of 14 is 7 and 7² is 49. So we add 49 and subtract 49, which means we are not changing the value of the quadratic. So we have x²+14x+49-49+2. This can be written: (x²+14x+49)-49+2, which is (x+7)²-47, which is answer a.
Answer:
see explanation
Step-by-step explanation:
Given that y varies inversely as x then the equation relating them is
y =
← k is the constant of variation
To find k use the condition that x = 9 when y = 15
15 =
( multiply both sides by 9 )
k = 135
y =
← equation of variation